An ensemble of state-of-the-art ash dispersion models: towards probabilistic forecasts to increase the resilience of air traffic against volcanic eruptions - Plu, M.; Scherllin-Pirscher, B.; Arnold Arias, D.; Baro, R.; Bigeard, G.; Bugliaro Goggia, Luca; Carvalho, A.; El Amraoui, L.; Eschbacher, K.; Hirtl, M.; Maurer, C.; Mulder, M.; et al. (Natural Hazards and Earth System Sciences, 2021)
High-quality volcanic ash forecasts are crucial to minimize the economic impact of volcanic hazards on air traffic. Decision-making is usually based on numerical dispersion modelling with only one model realization. Given the inherent uncertainty of such an approach, a multi-model multi-source term ensemble has been designed and evaluated for the Eyjafjallajökull eruption in May 2010. Its use for flight planning is discussed. Two multi-model ensembles were built: the first is based on the output of four dispersion models and their own implementation of ash ejection.